Finding Solutions to Environmental Problems A Process Guide - Wert, Jonathan M.; Magnoli, Michael A.; Mobile County Public Schools, AL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This guide is an attempt to provide a workable methodology for helping college students and citizen groups to identify the most pressing environmental problems in their communities and to find solutions to them. With some modification, it can also be used by high school students who are interested in independent or team studies. The monograph contains sections on: (1) problem-focused environmental education; (2) suggestions regarding problem solving; (3) suggestions for collecting and analyzing data or information; and (4) three projects for implementation. (RH)
Availability: Dr. Michael A. Magnoli, Coordinator, Environmental Education, Mobile County Public Schools, P.O. Box 1327, Mobile, Alabama 36601 (free).
ERIC Note: Not available in hard copy due to light and broken type throughout original document ; This quide was developed in the Environmental Education Section, Mobile County Public Schools.
Educational level discussed: Higher Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizen Participation; Environment; Environmental Education; Guides; Higher Education; Problem Solving; Reference Materials; Secondary Education; Guides, General